Treatment with 2 commercial antibiotics reduced clinical and systemic signs of pneumonia and the abundance of pathogenic bacteria in the upper respiratory tract of preweaning dairy calves - A.C.C.H. Tomazi; T. Tomazi; L. Bringhenti; A.P.A. Vinhal; M.X. Rodrigues; T.R. Bilby; H.J. Huson; R.C. Bicalho (Journal of Dairy Science, 2023)
ABSTRACT: The aim of this study was to evaluate the effect of therapeutically administered tildipirosin or florfenicol + flunixin meglumine for the treatment of bovine respiratory disease (BRD) accompanied by fever in calves before weaning compared with diseased and untreated animals. As specific objectives, we evaluated the composition of the bacterial microbiota of the upper respiratory tract (URT) and blood and health parameters of the animals. Preweaning Holstein female calves diagnosed with naturally acquired pneumonia were randomly assigned to one of the following experimental groups on the day of diagnosis (d 0): (1) TLD (n = 36): single subcutaneous injection with 4 mg/kg tildipirosin; (2) FLF (n = 33): single subcutaneous injection with an antimicrobial (40 mg/kg florfenicol) combined with a nonsteroidal anti-inflammatory drug (2.2 mg/kg flunixin meglumine); and (3) NEG (n = 35): no treatment within the first 5 d following enrollment. The NEG treatment group was closely monitored for 5 d, and calves were removed from the study following a standardized late treatment protocol, when necessary, to minimize health concerns. Healthy untreated calves (CTR; n = 31) were also selected for the study and used as controls. Blood samples used for biochemical analysis and nasopharyngeal swabs used for evaluation of URT microbiota were collected daily from d 0 until d 5 and then weekly until weaning. Next-generation sequencing of the 16S rRNA gene was used to assess the URT microbiota at the phylum and genus levels. Clinical signs associated with pneumonia and otitis media were assessed daily, as was the need for antibiotic interventions. Calves in the TLD and FLF groups had faster recovery from fever within the first 5 d after enrollment. In addition, antibiotic-treated calves reached the same serum haptoglobin levels as healthy calves on d 2 after diagnosis, whereas calves in the NEG group had higher haptoglobin levels than the CTR group until at least d 5 after BRD diagnosis. Calves in the TLD and FLF groups had a lower risk of treatment for pneumonia (FLF = 22.8%; TLD = 27.7%) from d 5 to weaning than calves in the NEG group (54.7%). Furthermore, FLF treatment had a significantly lower risk of nasal discharge, otitis media, and treatment failure compared with the NEG group, but did not differ from the TLD group. Differences in the composition of the URT microbiota were found between groups, and the genus Mycoplasma was the most abundant in samples collected from the URT of calves with and without pneumonia. Both drugs were effective in reducing the mean relative abundance (MRA) of important genera associated with pneumonia (Mannheimia and Pasteurella), although an increase in Mycoplasma MRA was observed for tildipirosin-treated calves. In conclusion, both drugs were effective in reducing the inflammatory signs of pneumonia and the need for antimicrobial treatment after enrollment compared with no treatment. In addition, both TLD and FLF were effective in reducing the MRA of important bacterial genera associated with pneumonia; however, TLD treatment was associated with increased Mycoplasma MRA compared with healthy and untreated calves.